2011
DOI: 10.2484/rcr.v6i4.601
|View full text |Cite
|
Sign up to set email alerts
|

Radiological pitfall: Siliconoma in internal mammary lymph node mimics breast cancer recurrence

Abstract: Siliconomas are rarely found in internal mammary lymph nodes in the context of ruptured, ipsilateral, silicone breast implants. However, they can sometimes cause a diagnostic dilemma, as in the presented case. We discuss the diagnostic pitfalls that can arise from misinterpreting a siliconoma for a metastatic lymph node, review the literature, and suggest appropriate diagnostic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
8
0
2
Order By: Relevance
“…On ultrasonography, silicone granuloma may show complex cystic lesions or a 'snowstorm appearance', depending on the amount of extravagated silicone gel and the extent of the fibrous and foreign-body reactions (1). Siliconomas in axillary, supraclavicular, or internal mammary lymph nodes may mimic the metastatic lymphadenopathy of breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…On ultrasonography, silicone granuloma may show complex cystic lesions or a 'snowstorm appearance', depending on the amount of extravagated silicone gel and the extent of the fibrous and foreign-body reactions (1). Siliconomas in axillary, supraclavicular, or internal mammary lymph nodes may mimic the metastatic lymphadenopathy of breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…Jafnframt geta fundist með segulómun merki um frítt silíkon í eitlum, jafnvel svokallað silíkonoma. 29 Ómskoðun á eitlum á hálsi eða í holhönd geta sýnt svokallaðan snowstorm effect sem endurspeglar sílíkonagnir innan um eðlilegan vef. 30 Eitlar sem teknir eru til smásjárskoðunar sýna gjarnan ósértaekar bólgubreytingar, oft með "götum" eftir aðskotahluti (silíkon).…”
Section: Klínískar Rannsóknir í Asia-heilkenniunclassified
“…Silicone-sensitive MR imaging sequences may also help to differentiate IT metastatic disease from silicone lymphadenopathy (34). At least one study showed that concurrent metastases were relatively rare in a small group of patients with silicone lymphadenopathy (35); however, these nodes should be carefully watched over time, as the presence of silicone in a lymph node does not preclude synchronous BC metastases.…”
Section: Differential Diagnosismentioning
confidence: 99%